A study of velocity, temperature, and density in the plasma generated by laser-induced breakdowns. (31st December 2019) - Nishihara, Munetake; Freund, Jonathan B; Elliott, Gregory S
Abstract: The paper presents velocity measurements of shock-induced flow field, leading to vortex generation and plasma deformation in air. Femtosecond-laser electronic excitation tagging (FLEET) velocimetry was performed at the times Δ t   =  3, 20, 50, and 100 µ s post laser-induced breakdown. Emissions over Δ t   =  3–10 µ s showed the propagations of the initially elliptic shock, transitioning into a spherical front. The shock emanated along the laser axis causes the flow outward, and then the pressure gradient generated by the rarefaction wave drives the inward flow at later moments, with the velocity magnitude approaching a steady-state value of 40 m s −1 . Temporal velocity evolution was compared with non-self-similar solutions behind the propagating shock, which are sensitive to the size of the energy deposition, and the use of the measured initial plasma diameter reproduced the experiment. There establishes a region of uniform velocity around 35 m s −1 in the air-flow running through the plasma, which triggers the roll-up of the plasma surface by a large-scale vortex, providing the detail of flow field evolution from the shock propagation to the plasma deformation. A collective Thomson scattering and hybrid fs/ps pure rotational coherent anti-Stokes Raman scattering (CARS) were also performed to gain insight into the high-temperature plasma. An effective electron–ion recombination rate of 2 10 −12 cm 3 s −1 was measured at Δ t   =  0.5–10 µ s, during a dynamic plasma expansion and compression. When the shock resides close to the plasma at Δ t   =  0.5–1 µ s, the temperature distributions were found to follow the similarity law.